The Digital Transformation Benefits and Comparison Between the Current and Past For Absher Platform and Elm - Almutairi, Saeed Mulawwah H (International Journal on Orange Technologies, 2023)
This research paper analyzes the current state of digital transformation in Saudi Arabia, focusing on the evaluation of progress and identification of areas for improvement. A conceptual analysis approach is used, examining the benefits of digital transformation, and conducting a comparative analysis of the Absher and ELM platforms. Data from academic databases, industry reports, and official documents is synthesized using thematic analysis. The findings highlight the need for key recommendations to advance digital transformation in Saudi Arabia. The main recommendations include strengthening privacy and security measures for platforms like Absher, improving user experience by streamlining processes and enhancing interfaces, bridging the digital divide through infrastructure development in rural and low-income areas, and fostering collaboration among government entities, private organizations, and technology providers. Additionally, enhancing digital skills and literacy through training programs for citizens, businesses, and government employees is essential. Continuous evaluation and updating of strategies, promoting transparency and accountability in the development and delivery of digital services, and fostering an innovation-friendly environment are also crucial. Implementing these recommendations will propel Saudi Arabia's digital transformation, ensuring privacy, improving user experience, reducing the digital divide, fostering collaboration, enhancing digital skills, and embracing innovation. These efforts will position the country as a leader in the global digital economy.